Aortic plaque burden predicts vascular events in patients with cardiovascular disease: The EAST-NOGA study. Issue 1 (January 2022) - Kojima, Keisuke; Komatsu, Sei; Kakuta, Tsunekazu; Fukamachi, Daisuke; Kimura, Shigeki; Fujii, Hiroyuki; Matsuura, Masayoshi; Dai, Kazuoki; Matsuoka, Hiroshi; Higuchi, Yoshiharu; Ueda, Yasunori; Asakura, Masanori; et al.
Highlights: Non-obstructive general angioscopy (NOGA) can diagnose aortic atherosclerotic plaques. Of 577 patients who underwent coronary angiography, 98% had at least one aortic plaque. Distribution of aortic plaque was most frequent at the infrarenal abdominal aorta. The number of aortic plaques detected by NOGA predicts subsequent clinical events. Aortic plaques (≥12) are a significant predictor for composite endpoint event. Abstract: Background: Non-obstructive general angioscopy (NOGA) can be used to diagnose aortic atherosclerotic plaques. We examine the association between the number of aortic plaques detected by NOGA and the risk of subsequent cardiovascular events. Methods: The Evaluation of AtheroScleroTic and rupture events by Non-Obstructive General Angioscopy (EAST-NOGA) was a prospective cohort study of patients with suspected coronary artery disease who underwent NOGA. Results: Of the 577 patients who underwent NOGA, 532 (92%) completed the follow-up (median follow-up: 13 months, interquartile range: 12-16). The median number of plaques per person was 6 (interquartile range: 3-12), and 567 (98%) had at least one aortic plaque. During the 13-month follow-up, 38 (7.1%) patients had a primary composite endpoint [including cardiovascular death, myocardial infarction, stroke, peripheral artery disease (PAD), or worsening renal function], which was significantly associated with chronic kidney disease, a history of PAD, a lower hemoglobin level, and large numbers of aortic plaques [11 (5-17) vs. 6 (2-11), p  = 0.003]. A receiver operating characteristic curve analysis for the number of aortic plaques predicting composite endpoints revealed that the cut-off value of aortic plaques was 12. After multivariate adjustment, the presence of ≥12 aortic plaques remained a significant predictor for composite endpoint events (hazard ratio 2.53, 95% confidence interval 1.26-5.04, p  = 0.010). Conclusions: The number of aortic plaques detected by NOGA may predict subsequent clinical events. Graphycal abstract: Image, graphical abstract